Micro-Focused Ultrasound on an Individual with Titanium Facial Implants: A Case Report - Panithaporn D (Clinical, Cosmetic and Investigational Dermatology)
Dissapong Panithaporn The Demis Clinic, Bangkok, 10330, ThailandCorrespondence: Dissapong Panithaporn, Email joedermato@gmail.comIntroduction: Both micro-focused ultrasound (MFU) and monopolar radiofrequency (MRF) interventions are relatively safe and well tolerated as a non-invasive approach to achieve rejuvenating effects, with patients reporting limited adverse effects. However, MRF uses an electrical current which can induce heating in metal, potentially causing burns or thermal injury in the skin or tissue around the implant, whereas MFU delivers focused high-energy ultrasound, which does not induce electrical currents in metal.Case Presentation: This report describes the case of a 28-year-old Thai male, who received titanium implants in the mandible bone, the mandible chin, the maxillary bone and the zygoma bone, seven years before. Because of his wish for a more sculpted and lifted facial appearance, the patient was treated with Ulthera Legacy in 2021 and with Ulthera Prime in 2024. With Ulthera Prime, visualization has significantly improved, which decreased the need to skip areas, leading to improved, more consistent results.Conclusion: This case study suggests that Ulthera Prime could be an option for skin firming and lifting effects for people with facial implants. Further research will be needed to corroborate this finding in a larger population.Keywords: Ulthera, micro-focused ultrasound, MFU, facial implants, titanium